BLOCKCHAIN AND ISLAMIC LAW: A COMPARATIVE ANALYSIS OF THE FOUR SUNNI SCHOOLS - Abdul Azis, Fakih (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
This study examines the perspectives of the four major Sunni Islamic legal schools—Hanafi, Shafiʿi, Maliki, and Hanbali—on the concepts of māl and ʿaqd and their implications for integrating blockchain technology within the framework of maqāṣid al-sharīʿah. Employing a normative–comparative approach, the study demonstrates that the Hanafi school adopts a relatively flexible conception of māl, grounded in social value and utility recognized by ʿurf, thereby allowing for the recognition of non-physical assets such as cryptocurrencies. By contrast, the Shafiʿi school maintains a more restrictive stance emphasizing physical existence and effective possession. The Maliki school recognizes manfaʿah as a legally protected interest while requiring a high degree of contractual clarity and the avoidance of speculation, whereas the Hanbali school advances the most expansive framework, grounded in maṣlaḥah and the presumption of permissibility in transactions. The study further argues that blockchain technology may contribute to the realization of the five core objectives of maqāṣid al-sharīʿah: ḥifẓ al-māl through transparency and decentralization, ḥifẓ al-ʿaql by mitigating gharar, ḥifẓ al-nasl through secure recordkeeping, ḥifẓ al-dīn by enhancing institutional accountability, and ḥifẓ al-nafs through improved data security and humanitarian aid distribution. Nevertheless, effective implementation requires robust Sharīʿah governance, ethical safeguards, data protection mechanisms, and coherent regulatory frameworks to ensure that technological innovation advances public usufruct while preventing harm.